Effects of Norepinephrine Infusion on Cutaneous Surface Temperatures of the Distal Extremities. Issue 3 (March 2021) - Nakamoto, Keitaro; Skaff, Paulina R.; McCully, Brian H.; Gress, Todd W.; Mozaffari, Farid B.; Denning, David A.
Abstract : Objectives: The etiology of vasopressor-induced digital necrosis is poorly understood, but the skin changes resemble those of frostbite, and it is known from experience that patients taking vasopressors have decreased digital temperatures. We aimed to examine the effects of norepinephrine use on surface temperatures of the distal extremities because there have been no studies examining this relation. Methods: Surface temperatures of all digits, palms, and soles were measured using an infrared thermometer in patients receiving different rates of norepinephrine infusion in the intensive care unit and compared with those not receiving any vasopressors. Results: A total of 101 measurements from 41 unique individuals were obtained. Temperature gradients between the core and the fingertips were consistently more pronounced in those receiving norepinephrine compared with those not receiving norepinephrine and increased with increasing rates of norepinephrine infusion, except with high-dose norepinephrine. Temperature gradients were more pronounced in the toes. Conclusions: Norepinephrine use was associated with greater core-to-fingertip temperature gradients and were more pronounced in the toes compared with the fingers.